Synaptic Density and Neuronal Metabolic Function Measured by Positron Emission Tomography in the Unilateral 6-OHDA Rat Model of Parkinson’s Disease - Raval, Nakul Ravi; Gudmundsen, Frederik; Juhl, Morten; Andersen, Ida Vang; Speth, Nikolaj; Videbæk, Annesofie; Petersen, Ida Nymann; Mikkelsen, Jens D.; Fisher, Patrick MacDonald; Herth, Matthias Manfred; Plavén-Sigray, Pontus; Knudsen, Gitte Moos; et al. (Frontiers in Synaptic Neuroscience, 2021)
Parkinson’s disease (PD) is caused by progressive neurodegeneration and characterised by motor dysfunction. Neurodegeneration of dopaminergic neurons also causes aberrations within the cortico-striato-thalamo-cortical (CSTC) circuit, which has been hypothesised to lead to non-motor symptoms such as depression. Individuals with PD have both lower synaptic density and changes in neuronal metabolic function in the basal ganglia, as measured using [11C]UCB-J and [18F]FDG positron emission tomography (PET), respectively. However, the two radioligands have not been directly compared in the same PD subject or in neurodegeneration animal models. Here, we investigate [11C]UCB-J binding and [18F]FDG uptake in the CSTC circuit following a unilateral dopaminergic lesion in rats and compare it to sham lesioned rats. Rats received either a unilateral injection of 6-hydroxydopamine (6-OHDA) or saline in the medial forebrain bundle and rostral substantia nigra (n=4/group). After three weeks, all rats underwent two PET scans using [18F]FDG , followed by [11C]UCB-J on a separate day. While [18F]FDG[18F]FDG uptake and [11C]UCB-J binding were both lower in the ipsilateral striatal regions compared to the contralateral regions., Using [11C]UCB-J, we could detect an 8.7% decrease in the ipsilateral ventral midbrain, compared to a 2.9% decrease in ventral midbrain using [18F]FDG. we found a larger difference in the ipsilateral striatum (8.9%) and ventral midbrain (8.7%) for [11C]UCB-J, compared to [18F]FDG (5.7% and 2.9% respectively). Differential changes between hemispheres for [11C]UCB-J and [18F]FDG outcomes were also evident in the CSTC circuit’s cortical regions, especially in the orbitofrontal cortex and medial prefrontal cortex where higher synaptic density yet lower neuronal metabolic function was observed, following lesioning. In conclusion, [11C]UCB-J and [18F]FDG PET can detect divergent changes following a dopaminergic lesion in rats, especially in cortical regions that are not directly affected by the neurotoxin. These results suggest that combined [11C]UCB-J and [18F]FDG scans could yield a better picture of the heterogeneous cerebral changes in neurodegenerative disorders.